The Nargun and the stars - Wrightson, Patricia, 1921-2010. ([Richmond, Vic.] : Hutchinson of Australia, 1974)
An ancient stone creature threatens the lives of a family on a lonely sheep farm in Australia.
Children's Book of the Year, 1974.
White
For children.
Keywords: Aboriginal Australians -- Religion -- Juvenile fiction; Farm life -- Australia -- Juvenile fiction; Environmental degradation -- Juvenile fiction; Spirits -- Juvenile fiction; Australia -- Juvenile fiction; Australian; Fantastic fiction; Children's stories, Australian